(untitled) (Geographical Journal of Nepal, 2011)
The post-Jomtien period has witnessed a rising concern in the quality of primary education. This paper attempts to examine the quality of primary education and its association with the incidence of dropout from schools School survey form was administered to collect the necessary information from seventy two schools in Doti and Rautahat districts of Nepal. The significant indicators of dropout from schools are Toilet for girls, adequate teachers, committed and motivated teachers in profession, primary school curriculum, use of local teaching materials, 90+ pass rates, parental support to school, 90+ student attendance rates and regular school supervision by DEO. These indicators are found statistically significant with regard to the dropout rate as grouping variable. Therefore, dropout was found low in good quality schools with relatively better separate toilet for girls, adequate teachers, school having curriculum and teaching materials, and provision of 90 percent and above attendance rate of students. The Geographical Journal of Nepal, Vol. 8-9, 2010-2011: 23-32